NATIONAL TEAMS RANKING BASED ON SITUATIONAL EFFICIENCY INDICATORS OF THE OFFENCE AT THE WORLD HARDBALL CHAMPIONSHIP - Sanja Bajgorić,; Muris Dug,; Nina Bijedić,; Samra Mededovic, (Sport Scientific And Practical Aspects, 2025)
T his study was based on the 45 games of the 2013 World Junior Handball Championship in Bosnia and Herzegovina. The focus was on the determination of the difference in the scope of the situational efficiency of offence between national teams: Sweden, Spain, France, Croatia and Bosnia and Herzegovina. Following variables were analysed: KPKUK – total number of the contra offences and semi counter offences, ŠPNAUK – total number of shots from positional offence, NAUKM7 – total number of the 7m in offences, BRZNAUK – total number of the rapid offences, BRZCUK – total number of the fast centres, and five variables for assessment of the situational efficiency in successful offences: KPKUS – total number of the successful contra offences and semi counter offences, ŠPNAUS – total number of the successful shots from positional offence, NAUSM7 – total number of the successful 7m in offences, BRZNAUS – total number of the successful rapid offences, BRZCUS – total number of the successful fast centres. The aim of this study was to determine differences of the situational efficiency of analysed national teams, and to rank national teams by percentile of means using analysed variables. The game quality of the analysed national teams was determined on the results of the central and dispersion parameters and same analysed national teams were ranked on the obtained values of the parameters.